Pengaruh Mastikasi Karet Terhadap Karakteristik Campuran Aspal - Karet Spesifikasi Teknis (Crumb Rubber) - Arya Wiranata; M. Iwan Fermi; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The use of natural rubber in the form of solids such as crumb rubber (SIR 20) will require a long time when mixing with asphalt, therefore mastication process is used before mixing with asphalt. Mastication is process of grinding natural rubber in open mill to break the chain in natural rubber polymer. The aim of this study to determine the effect of rubber mastication and rubber storage time after mastication on modified asphalt characteristics. In mastication process, asphalt as plasticizer agents with levels of 0%, 1%, 2%, 3%, 4% and 5% w/w and rubber storage time after mastication are 0 days and 30 days. The asphalt used is 60/70 penetration type asphalt. Asphalt modified by mixing SIR 20 and asphalt with a ration of 1:9 at temperature of 165oC and stirring time for 30 minutes. Modified asphalt is tested for penetration test, softening point, marshall stability, and weight loss. The results of the study showed that the addition of plasticizers in rubber and rubber storage time after mastication affected the value of penetration, softening point, marshall stability, and weight loss. The best results were obtained at 0% plasticizer content and 0 days rubber storage time with a Penetration value of 58.5 dmm, Softening Point 59.1ºC, Marshall Stability 1710.9 kg, and Weight Loss 0%. The storage time of 30 days, the best results on a 5% plasticizer content with a Penetration value of 58.4 mm, Softening Point 56.3ºC, Marshall Stability 1463.3 kg, and Weight Loss 0.27%.Keywords : asphalt modification, plasticizer, mastication, SIR 20, penetration, softening point, marshall stability